2015
DOI: 10.1007/s00217-015-2516-9
|View full text |Cite
|
Sign up to set email alerts
|

The bioavailability of calcium in the form of pyruvate, carbonate, citrate–malate in healthy postmenopausal women

Abstract: administration with the greatest values observed for the former. All the studied formulas decreased the intact parathyroid hormone level in serum although the greatest change was observed for CaPyr and CaCarb. The administration of CaPyr induced gastrointestinal side effects, dyspepsia and diarrhea in 16.6 % of the studied individuals. No serious adverse events were noted. CaPyr demonstrates both a promising source of Ca and a potential for use in osteoporosis prevention. Further investigations should focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A cohort study reported that amino acid metabolism, such as tyrosine and tryptophan metabolism, was significantly related to gut dysbiosis and osteoporosis (68). Pyruvate also plays a pivotal role in various physiological processes as a counterion and could affect the absorption and availability of calcium through the epithelial cells (69).…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study reported that amino acid metabolism, such as tyrosine and tryptophan metabolism, was significantly related to gut dysbiosis and osteoporosis (68). Pyruvate also plays a pivotal role in various physiological processes as a counterion and could affect the absorption and availability of calcium through the epithelial cells (69).…”
Section: Discussionmentioning
confidence: 99%
“…In order to increase calcium solubility, certain authors prepared nanocarriers using CaCO 3 –cyclodextrin complexes (Kurapati & Raichur, 2013). Some scientists also studied the possibility to increase calcium bioavailability by using sources of calcium with various solubilities, such as calcium pyruvate and calcium citrate malate or calcium malate, calcium lactate, calcium fumarate, calcium lactate malate, and calcium lactate citrate (Rzymski et al., 2016).…”
Section: Gastrointestinal Factors Affecting the Nutraceutical Bioavaimentioning
confidence: 99%
“…Thus, the search for effective IBS therapeutic strategies remains a significant clinical challenge. Therefore, the aim of the present study was to evaluate the potential use of stable and pure CPM in the treatment of a model of post-inflammatory IBS, which has previously reported to exert intestinal anti-inflammatory effects in acute and chronic murine models of colitis, and to be a form of calcium supplementation for the treatment of osteoporosis in postmenopausal women with good bioavailability and tolerability [5,19]. With this purpose, the effects of CPM have been evaluated in a rat model of chronic post-inflammatory visceral pain induced by deoxycholic acid (DCA) that results in persistent visceral hyperalgesia and referred pain in rats, modelling some aspects of post-inflammatory IBS in humans [20].…”
Section: Introductionmentioning
confidence: 99%